Endometrioid Adenocarcinoma of Caecum Causing Intussusception. (28th April 2013) - Verma, Rashmi; Osborn, Sally; Horgan, Kieran
Abstract : Malignant transformation of endometriosis is rare and is usually seen in ovarian endometriosis. The colon and rectum are the most common sites for extragonadal endometriosis, and although serosal involvement is commonly seen, mucosal involvement is rare. Malignant transformation of endometriosis is a rare but a well-known complication of endometriosis. We report an unusual presentation of endometrioid adenocarcinoma with lymph node metastasis, arising from endometriosis in the caecal wall and causing ileocaecal intussusception. The patient presented with sudden onset of abdominal pain with features suggestive of acute appendicitis. Diagnostic laparoscopy revealed an ileocaecal intussusception. Conversion to open surgery confirmed a caecal mass causing ileocaecal intussusception, and a radical right hemicolectomy was performed. Histology revealed endometrioid adenocarcinoma arising in a focus of endometriosis in the muscularis propria and involving the mucosa, with one regional metastatic lymph node.